THE CORRELATIONS AMONG METACOGNITIVE READING STRATEGIES, READING INTEREST, AND READING ACHIEVEMENT OF THE EIGHTH GRADE STUDENTS - Shafitri Indah Pratiwi; Tahrun Tahrun; Masagus Firdaus (Universitas Muhammadiyah Makassar, 2023)
The aims of this study were to figure out the correlation between: a) students’ metacognitive reading strategies and their reading achievement, b) students’ reading interest and their reading achievement, and c) the students’ metacognitive reading strategies, reading interest, and their reading achievement of descriptive text. This research also analyzed the contributions of independent variables toward students’ reading achievement. There were 130 students of the eighth grade involved as the samples and were selected through simple random sampling. This study employed quantitative method of correlational research design. Two questionnaires and one reading test were used to collect the data. The data obtained were analyzed by using Simple Correlation of r-Product Moment and Multiple Regression analysis. The analysis of the data showed that there was a 4.1% contribution of the students’ metacognitive reading strategies to their reading achievement, with a sig. value of 0.02 and being less than 0.05. Reading interest contributed 7.8% toward students' reading achievement, with the correlation between reading interest and reading achievement being 0.01, which was lower than 0.05. The correlations among metacognitive reading strategies, reading interest, and reading achievement were 0.003, which was less than 0.05, and both metacognitive reading strategies and reading interest contributed 8.5% to students' reading achievement. Thus, it can be stated that there were correlations among the eighth grade students at SMP Negeri 39 Palembang's metacognitive reading strategies, reading interest, and reading achievement.